2020
DOI: 10.1038/s41598-020-61856-9
|View full text |Cite
|
Sign up to set email alerts
|

Surface passivation of zero-mode waveguide nanostructures: benchmarking protocols and fluorescent labels

Abstract: Zero mode waveguide (ZMW) nanoapertures efficiently confine the light down to the nanometer scale and overcome the diffraction limit in single molecule fluorescence analysis. However, unwanted adhesion of the fluorescent molecules on the ZMW surface can severely hamper the experiments. Therefore a proper surface passivation is required for ZMWs, but information is currently lacking on both the nature of the adhesion phenomenon and the optimization of the different passivation protocols. Here we monitor the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 72 publications
3
23
0
Order By: Relevance
“…We argue that, for the Atto550 and Atto633 cases, this unspecific signal is a direct consequence of the unspecific interaction of the fluorophore per se with cell membranes, as reported by other studies (Bosch et al, 2014;Hughes et al, 2014). This in turn may depend on the higher hydrophobicity in general displayed by Atto dyes when compared, e.g., to Alexa dyes [ Supplementary Table 1 and (Patra et al, 2020)]. Furthermore, these two fluorophores bring a net positive charge in physiological conditions ( Supplementary Table 1) which could also promote adhesion to cell membrane.…”
Section: Comparative Study Of S6-trka Labeling By Different Coa-fluorsupporting
confidence: 52%
“…We argue that, for the Atto550 and Atto633 cases, this unspecific signal is a direct consequence of the unspecific interaction of the fluorophore per se with cell membranes, as reported by other studies (Bosch et al, 2014;Hughes et al, 2014). This in turn may depend on the higher hydrophobicity in general displayed by Atto dyes when compared, e.g., to Alexa dyes [ Supplementary Table 1 and (Patra et al, 2020)]. Furthermore, these two fluorophores bring a net positive charge in physiological conditions ( Supplementary Table 1) which could also promote adhesion to cell membrane.…”
Section: Comparative Study Of S6-trka Labeling By Different Coa-fluorsupporting
confidence: 52%
“…Moreover, advanced nanofabrication approaches enable the preparation of hybrid devices that integrate both solid-state and biological elements (such as organic coatings or functional proteins). 79,80 Future development in nanocavities engineering might include the exploration of highindex dielectric materials for the fabrication of dimers, 81,82 and their integration with MNPs. 83 Other directions might include the combination of dimers and NPoM structures, so called dimers-on-lm, in order to obtain narrow resonances through the superposition of bright and dark modes.…”
Section: Discussionmentioning
confidence: 99%
“…The mPEG-SH is prepared at 20 μM concentration in 1× phosphate-buffered saline (PBS) pH 7.5 and was allowed to react with the gold surface for three hours at room temperature. The choice of 2 kD PEG was based on a recent study of passivation effects, where it was found that positively charged dyes such as Atto647 adhere to sample surfaces unless the surface is passivated with PEG longer than 0.5 kD and shorter than 5 kD [ 74 ]. The ZMW were rinsed with ultra pure water.…”
Section: Methodsmentioning
confidence: 99%